x2+-2x+-1=0

Simple and best practice solution for x2+-2x+-1=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x2+-2x+-1=0 equation:



x2+-2x+-1=0
We add all the numbers together, and all the variables
x^2-2x=0
a = 1; b = -2; c = 0;
Δ = b2-4ac
Δ = -22-4·1·0
Δ = 4
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$\sqrt{\Delta}=\sqrt{4}=2$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-2)-2}{2*1}=\frac{0}{2} =0 $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-2)+2}{2*1}=\frac{4}{2} =2 $

See similar equations:

| 12x+1=360 | | 23+8x=-3(3-7x) | | 15/4z+1/4=4 | | m+11/8=3 | | 4x+5=11x+9 | | x+-9x=0 | | 5x-6=109 | | j/3-16=-14 | | 3y=9=15 | | X+10x2=22 | | 2(3r+40)-3(r+1)=11 | | 5+2q=15 | | 16-3x=10x-5x+8 | | 2x+5=4x-23 | | u/3+6=8 | | 8=7+y | | u/3+9=12 | | 8=7=y | | 12 = u3+ 9 | | .5x-6=0 | | 4(2y+1)-9(y-1)=3 | | k/17=35 | | 3g+4=7g-6 | | 3x+4=19,x | | 6x-13=-2x+ | | v-2+ -1= -3 | | 4(2y+1)-9(y-3)=3 | | 4(2x+3)=2(3x–4) | | |s–1.75|=0.02 | | 7x-5=10x-6 | | 2x-10=5-5 | | 10x+12=13+18 |

Equations solver categories